Transforming Autism Spectrum Disorder Care: The Role of Artificial Intelligence in Diagnosis and Treatment - Li, Mengyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
The diagnosis and treatment of autism spectrum disorder (ASD) are highly challenging, demanding extensive preventative and intervention plans. With an emphasis on the use of artificial intelligence (AI) technology, this study aims to look into efficient prevention and therapy approaches for ASD. The study highlights the shortcomings in the present approaches and emphasizes the significance of early diagnosis and intervention. Using a mixed-method approach, the study looks at the effectiveness of different treatment methods and AI-driven diagnostic tools using case studies and a thorough literature review. The methodology includes a detailed analysis of peer-reviewed research papers, clinical trials, and actual AI implementations in ASD care. The results show that AI can improve outcomes for people with ASD by enhancing diagnostic accuracy and customizing therapies. The study additionally investigates at how AI-powered assistive technology, including interactive applications and social robots, can help people with ASD. Additionally, the viability and moral implications of incorporating AI-based solutions into clinical practice are looked at. The paper ends with suggestions for integrating AI into clinical procedures and future lines of study to confront the dynamic nature of ASD therapy. The study intends to give an extensive understanding of how AI may transform ASD care, making it more accurate, tailored, and efficient by addressing these factors.